Comparative Effectiveness of Standard versus Patient‐Centered Collaborative Care Interventions for Depression among African Americans in Primary Care Settings: The BRIDGE Study. (20th June 2012) - Cooper, Lisa A.; Ghods Dinoso, Bri K.; Ford, Daniel E.; Roter, Debra L.; Primm, Annelle B.; Larson, Susan M.; Gill, James M.; Noronha, Gary J.; Shaya, Elias K.; Wang, Nae‐Yuh
<x xml:space="preserve">Abstract</x> Objective To compare the effectiveness of standard and patient‐centered, culturally tailored collaborative care (CC) interventions for African American patients with major depressive disorder (MDD) over 12 months of follow‐up. Data Sources/Study Setting Twenty‐seven primary care clinicians and 132 African American patients with MDD in urban community‐based practices in Maryland and Delaware. Study Design Cluster randomized trial with patient‐level, intent‐to‐treat analyses. Data Collection/Extraction Methods Patients completed screener and baseline, 6‐, 12‐, and 18‐month interviews to assess depression severity, mental health functioning, health service utilization, and patient ratings of care. Principal Findings Patients in both interventions showed statistically significant improvements over 12 months. Compared with standard, patient‐centered CC patients had similar reductions in depression symptom levels (−2.41 points; 95 percent confidence interval (CI), −7.7, 2.9), improvement in mental health functioning scores (+3.0 points; 95 percent CI, −2.2, 8.3), and odds of rating their clinician as participatory (OR, 1.48, 95 percent CI, 0.53, 4.17). Treatment rates increased among standard (OR = 1.8, 95 percent CI 1.0, 3.2), but not patient‐centered (OR = 1.0, 95 percent CI 0.6, 1.8) CC patients. However, patient‐centered CC patients rated their care manager as more helpful at identifying their concerns (OR, 3.00; 95 percent CI, 1.23, 7.30) and helping them adhere to treatment (OR, 2.60; 95 percent CI, 1.11, 6.08). Conclusions Patient‐centered and standard CC approaches to depression care showed similar improvements in clinical outcomes for African Americans with depression; standard CC resulted in higher rates of treatment, and patient‐centered CC resulted in better ratings of care.